Reaping pericarp browning-free litchi - Barman, Kalyan; Patel, V B; Sharma, Swati (Indian Horticulture, 2019)
Litchi fruits have a bright red pericarp upon harvesting that turns brown during shipping and storage. Pericarp browning is a major post-harvest problem, which results in reduced shelf-life and commercial value of fruits. This browning is generally attributed to rapid degradation of anthocyanin pigments, change in cellular pH, desiccation from the peel and development of micro-cracks. Commercially, fruit colour is preserved by sulphur dioxide fumigation. However, due to increasing consumers concern over harmful residue of sulphur and its undesirable effect on fruit quality, safe alternative treatments like surface coating, acidification and modified atmosphere packaging can be used to delay pericarp browning and maintaining post-harvest quality of litchi.